Sociološka anketna raziskava Prenova stanovanjskih sosesk v Ljubljani - Savsko naselje - Trček, Franc (Urbani izziv, 2005)
The article presents some key findigs of the sociological survey research Rehabilitation of housing estates in Ljubljana - Savsko naselje. It focused onattitudes and opinions of the estate''s residents and estimated their future residential preferences. The key issue - coupled with significant distrust of the local authority as well as the interdisciplinary group of experts conducting the research - was above all the inability of the residents to finance rehabilitation, but also their vigourous resentment of any co-financing that would entail extensions or even new construction. The surveyresults show that, if the rehabilitation process is not undertaken comprehensively, including acceptable financial-loan arrangements, in the nextdecade the quality of maintenance will drop and consequentially the value of property in the neighbourhood.
Keywords: bivalno okolje; Ljubljana; prenova; Savsko naselje; stanovanjska naselja; urbana sociologija